Diagnóstico situacional turístico de la parroquia rural paletillas del cantón Zapotillo de la provincia de Loja - Cueva Carrión, Alberto Francisco (2016)
In Ecuador the southwest of the province of Loja, in the county is rural Zapotillo Paletillas parish. Paletillas the same features Natural and Cultural resources that can be exploited for tourism is why conducting a Situational Tourist diagnosis that can serve as reference for the creation of tourism projects that improve the quality of life of its inhabitants raised . Given that the tourism diagnosis is established as an experiential activity that involves a group of people of a people or institution interested in presenting solutions to problems or conflict situations, submitting to an analysis that should lead to a concrete plan of action to solve the problematic situation. To do various surveys to Paletillas parish in which The fragility of a tourist diagnosis that allows for an extensive study of tourism that takes place in this community, valuing tourism resources has made the parish. In order to analyze and determine the weaknesses and potentials having the Paletillas parish, wont general objective of this study, the identification of alternative tourism development Paletillas parish of the canton Zapotillo through a tourist diagnosis, and three targets specific they are: they characterize the current situation of tourism in the Rural parish Paletillas canton Zapotillo with its opportunities and constraints, determine the composition of the tourism supply and demand of the parish, and finally, design strategies for tourism development in the Paletillas parish. To fulfill the first objective taking into account various methods and techniques such as the scientific method, analytic-synthetic and literature. And techniques such as interview, direct observation, plus tools that helped define the place of study, with reference to the "Handbook of Local tourist diagnosis" Carla Ricaurte were used. The same as the requirements to be applied as required by the parish Paletillas matrices was subtracted. To determine the second target will take into account the scientific methods, literature and direct observation technique also was considered as a fundamental tool methodology for lifting information attractions of the Ministry of Tourism of Ecuador, as this to determine the tourist offer of the parish. For the analysis of tourism demand of the parish survey technique was used, it was applied to the tourists who come to Paletillas parish, to get the exact number of surveys that would apply were taken as reference records tourist department Zapotillo canton. Finally for the development of the third objective method of rapid analysis and participatory planning MARPP, which consisted of conducting a participatory workshop where stakeholders participated in the design of a SWOT matrix was used, the result allowed establishing tourism development strategies by planning tourism projects to boost tourism parish Paletillas process, improving the quality of life of its inhabitants. The results obtained are found to be able to integrate the components of the tourism system collecting the necessary information, the determination of the offer shows the tourist potential: Waterfall or Añalcal Lobos, Parroquialización parties, religious festival of the Virgin of the Rosary , commercial holiday and cuisine as Sango, dry Goat, corn chicha. Based on the information collected it was concluded that the Paletillas parish has great tourism potential with cultural and natural attractions, which can be exploited for tourism by improving the tourism infrastructure, improving signaling attractions and training people for the attention of tourists there is also lack of support from public institutions related to tourism, currently only receives the Illustrious Municipality of Zapotillo. Whereas, it is recommended to the parish and its inhabitants, make tourism resources they possess, with tourism businesses undertaking, training residents to prepare as guides, customer service and make massive campaigns, using media more effective. First of all to the Vestry and who wishes to take account of this research work as a basis for future tourism development projects of Paletillas Parish.